Terminalia ferdinandiana inhibited the increased of matrix metalloproteinase-1 and prevent collagen decreased in mice skin exposed to UV-B - Shalihaty Emy; Ida Sri Iswari; Ni Wayan Winarti (Indoscholar, 2021)
Background: Kakadu cream contained 0,1% Kakadu plum (Terminalia ferdinandiana) extract with a high content of phenolic compound, flavonol, tocopherol, luthein, chlorophyll, and ellagic acid has potential to prevent the Ultraviolet-B (UV-B) effect on skin aging acceleration. To date, there’s no in vivo experiment on the effect of kakadu plum extract on collagen nor matrix metalloproteinase-1 (MMP-1). This research aims to evaluate the effectiveness of Kakadu cream administration in inhibiting the increase of MMP-1 expressions and prevent the decrease of collagen amount in mice (Mus musculus) skin exposed to UV-B. Methods: An experimental study with a post-test only control group design was employed in 36-male-mice, 6-8 weeks old, weighing 20-25 grams. The samples were divided randomly into two groups, a control group given base cream and the study group, given Kakadu cream 0,1% on their shaved backs, 1 cm2 in size as the UV-B exposure's location. The UV-B irradiation was done three times a week for 4-weeks. The base and Kakadu cream were given twice a day. Comparative analysis was carried out to compare MMP-1 expression and collagen amount in both groups. Results: The results show that the mean of MMP-1 expression on the study group was significantly lower compared to control group (p<0.001). The mean collagen amount was significantly higher in the study group than in the control group (p< 0,001). Conclusion: From the results, can be concluded that Kakadu cream inhibited the increase MMP-1 expression and prevent the decrease of collagen amount in mice skin exposed to UV-B.